Physico-chemical properties and metabolizable energi value of protein concentrate from palm kernel meal in broiler. - Ramli, Nahrowi; ., Yatno; Hasjmy, A.D; ., Sumiati; ., Rismawati; Estiana, R (Indonesian Animal Sciences Society, 2008)
Protein concentrate from palm kernel meal (BIS PRO) was produced using combination method of grinding and ethanol extraction. The experiment was conducted to evaluate physico-chemical properties and metabolizable energy value of BIS PRO in broiler. The metabolizable energy experiment was conducted in Completely Randomized Design using 19 broilers Ross strain with average body weight of 1.79 Â± 0.11 kg. The treatment diets were: R1(90 % basal diet + 10% palm kernel meal), R2 (90% basal diet + 10% BIS PRO) and R3 (90% basal diet + 10% soybean meal).The result showed that BIS PRO had higher specific density (0.723 g/ml), compacted specific density (0.885 g/ml), specific gravity (1.596 g/ml), and angle of repose (28.320) compared to those of palm kernel meal and soybean meal. Total solubility of BIS PRO (70.22%) were higher than that of the others. BIS PRO had metabolizable energy of 1.94 â 2.66 time higher compared to metabolizable energy of palm kernel meal, but there was no difference compared to metabolizable energy of soybean meal. It is concluded that BIS PRO has physicochemical properties and metabolizable value better than that of palm kernel meal and were equal to that of soybean meal. Â Key Words: Physico-Chemical Characteristics, Protein Concentrate, Palm Kernel Meal, Metabolizable Energy, Broiler